Robótica educacional e aprendizagem colaborativa no ensino de biologia: discutindo conceitos relacionados ao sistema nervoso humano - Garcia, Mara Cristina de Morais (2015)
The educational robotics is a pedagogical action that uses the learning of scientific concepts by the students through interaction with a robot collaboratively. The objective is to design and develop robots reusing materials to discuss biology concepts in a playful learning environment at how the educational robotics facilitates student learning the average level of education. This is a qualitative research of a case study. Participants are teenagers sixteen years on average, volunteers who participated in weekly meetings against the turn. The construction of the robot that represents the human nervous system was proposed by the students. Their participation has gone beyond the concept of the discussion and it was possible from the construction of the prototype. We note that collaboration is a major feature present in the activity. However it is important to clarify that the cooperation of the collaboration assumptions also attended the activity. From designing the robot until its completion, we see the awakening of student interest, along with a natural increase of motivation of both the group and the teacher involved.